The Managerial Mechanism of Future Competitive Technical Specialists Vocational Training: the Russian Experience - Akhmetov, Linar G.; Kirillova, Olga V.; Kirillova, Tatiana V.; Varlamov, Aleksey V.; Kashina, Svetlana G.; Safin, Rais S.; Leonova, Elena V.; Sharonov, Ivan A. (International Review of Management and Marketing, 2016)
The relevance of the paper is reasoned by the search for adequate mechanisms to manage vocational training of future competitive technical specialists. Modern economies demand the training of technical specialists' new generation ready to project and engineering, production and technological, organizational and management, science and research, service and operational professional activities, as well as the fulfillment of skilled work using modern equipment for the developed technological process. One of the variants of the organization of vocational training of future competitive technical specialists is based on the integration of educational curricula of different levels (primary, secondary and high). The purpose of the paper is to develop a managerial mechanism for future competitive technical specialists' training based on the integration of educational curricula at different levels (primary, secondary and high). The leading method is the method of action research (AR), allowing obtain new knowledge on the managerial mechanism for vocational training of specialists, capable of a certain type of practical activities, self-organization and competitiveness on the labor market through the integration of primary, secondary and high levels of educational curricula. The article defines the essence of integrated educational curricula of primary, secondary and high levels of vocational training; it justifies the organization of control and assessment procedures of students' vocational training through the integration of educational curricula at different levels; proposes an algorithm of students' selection to study on integrated educational curricula. Paper Submissions can be useful for research and teaching staff of technical specialists' vocational training system, experts of training and retraining centers in the training content's selection and structuring of research universities' scientific and pedagogical staff development. Keywords: Integration, Levels of Vocational Training, Management, Technical Specialists. JEL Classifications: A23, I23, I26